Co-design of a digital 24-hour time-use intervention with older adults and allied health professionals - Henry T. Blake; Aaron Davis; Maddison L. Mellow; Melissa Hull; Bethany Robins; Kate Laver; Kate Laver; Dorothea Dumuid; Timothy Olds; Hannah A. D. Keage; Lui Di Venuto; Ashleigh E. Smith (Frontiers in Digital Health)
Using co-design principles based on the Health CASCADE framework, we aimed to describe the collaborative process undertaken to develop a 24-hour time-use intervention, called Small Steps, which promoted gradual and incremental health-behavior change. A secondary aim was to reflect on the challenges and benefits of co-design in this project, offering insights into the “why” and “how” to co-design 24-hour time-use interventions with priority populations. Twelve participants were invited and participated in 6 co-design workshops (June 2023–January 2024). To prioritize older adults’ views in the end-product, 8 adults aged >65 years (the target population) and 4 allied health professionals with >2 years’ experience working with the target population were recruited. Workshops and activities were structured using the British Design Council's Double Diamond Design Process to stimulate design thinking. Where possible, participant-led documentation was used to reduce the bias associated with academic scribing and empower participants to provide input and facilitate ownership for the project. Workshop activities and discussions were captured through printouts, audio and iPad screen recordings and analyzed through reflexive thematic and content analysis. Co-designers contributed to all elements of the intervention including the website design, the content, and the level of researcher input during the intervention. Iterative improvements were made based on the unique perspectives and needs of the community experts. During the action planning process, older adults wanted both support and autonomy, while maintaining the freedom to adapt these options to their individual needs. Older adults also preferred a step-by-step approach, allowing for gradual behavior changes across the intervention to avoid feelings of becoming overwhelmed. The co-design process enabled the tailoring of the Small Steps intervention to the specific needs of its intended audience. Key factors contributing to the co-design included flexibility in the design process, fostering a supportive environment, and empowering participants through activities that guided and stimulated their thinking. These elements not only helped shape the development of Small Steps but reinforced the value of co-design in developing personalised interventions for older adults.